TRANSLATION METHODS OF PHRASAL VERBS IN SUBTITLES OF THE COCO MOVIE - Arie Wijayanto; Evert Hilman (PROJECT (Professional Journal of English Education), 2023)
This study aimed to find out the type of phrasal verb and translation methods used by translators in translating phrasal verb in subtitles of the Coco movie. This study is based on chesterman's theory from "Memes of Translation" book, as well as several other theories such as catford, and Nababan have been used to find out the answer in the analyzing process. This descriptive analysis research took the data from subtitles of the COCO movie as the research material. The research results on 95 data of phrasal verb consist of fifty five data of intransitive inseparable phrasal verb, twenty five data of transitive inseperable phrasal verb and fifteen data of transitive seperable phrasal verb. There are eighty eight data using Unit shift and seven data using literal translation. For the assessment of the quality of translation on the 95 data shows a very high level of accuracy, only 5 data show less accuracy level, and 90 data indicates high accuracy level, high acceptability level, and high readability level.Â Keywords:Â  Phrasal Verb; Translation Assiment; Translation; Translation Method